ANALISA PRODUKTIFITAS PEMASANGAN SCAFFOLDING UNTUK TEMPAT BEKERJA - udi subagyo (Prokons: Jurnal Teknik Sipil, 2019)
Abstract Prefabricated scaffolding (Scaffolding) is a scaffold that has been formed from a factory with a typical dimension. This makes scafolding tends to be faster and uses less labor in its implementation. The construction project of scaffolding installation of productivity value and OH coefficient is very necessary in calculating the work budget plan and the Work Unit Price Analysis in the Public Works sector, there is no productivity analysis about the work of installing scaffolding.This study will conduct a Productivity Analysis of Scaffolding Installation for Workers' Places with the aim of Gaining time, relationships and productivity values and coefficients. OH with variations in the number of workers and variations in the structure of scaffolding in the installation of scaffolding for workplaces.The results obtained in this study are the relationship of the time needed for the installation of scaffolding at all steps, the greater the number of bays the more time is needed and the more labor time the installation time and productivity value for installation of 1 step scaffolding is 73,879 m2 / day , 2 Step is 57,497 m2 / day, 3 Step is 48,645 m2 / day, 4 Step is 42,130 m2 / day and productivity value decreases with increasing Step number, while OH value increases as the number of Step increases. And the value of the OH coefficient as the number of steps increases is Coef. OH = 0,0214.Step - 0,0081. Keywords: scaffoding, productivity, coefficient, OH